Realizing the potential of Bangladesh through economic corridor development. - Hong, Soon Chan (Metro Manila, Philippines Asian Development Bank, 2018)
Economic corridor development in Bangladesh is presented as an effective policy to promote sustainable economic growth.Bangladesh needs a holistic development strategy such as economic corridor development to drive structural transformation and regionally balanced development. Economic corridor development is an appropriate integrative strategy for the country as it is proven to be an effective tool to enable industrial proliferation, create jobs, upgrade infrastructure, align infrastructure development with urban and social agglomerations, unify domestic markets, and link production centers with global value chains. Economic corridors would decentralize development away from Dhaka and Chattogram, create jobs, and create markets in regions lagging behind.
Keywords: Sustainable development -- Bangladesh; Electronic books